Jogos no ensino de matemática: uma análise na perspectiva da mediação - Andrade , Kalina Ligia Almeida de Brito (2017)
The present research had as main objective to analyze the use of games in the teaching of Mathematics, in the initial years of Elementary School, considering the perspective of pedagogical mediation. In the theoretical scope we deal with the conceptions of mediation in Vygotsky, inserting the discussion about the game as mediating instrument; We bring a historical clipping about the development of the game concept; And we briefly discuss the processes of teacher formation to teach Mathematics, as well as some considerations about the textbook. We traced the path of qualitative research and the observation environment were classrooms in grades 3 and 5 of Elementary School. They participated in the investigation, besides teachers of these years of schooling, teachers of a course of Pedagogy, with the perspective of discussing the formation for the use of pedagogical games in the classes of Mathematics. For analysis of the interviews we take as reference the analysis of content of Bardin. In our argumentation about the results of the interviews, we articulated with the results of the analysis of the collection of textbooks of Mathematics adopted by the teachers of the highlighted years, understanding them as an important resource to support the planning of teaching activities. We evaluated in the textbooks the authors' proposal for the use of games in relation to the mathematical contents associated with them. The analysis of the interviews and textbooks, as well as the observations of the classrooms, strengthened the defense arguments of our thesis, that the game is only a mathematical learning mediation tool if there is an effective conjunction of guidelines, considering Teacher training, initial and / or continuing, and the proposals of the Mathematics textbooks. We identified gaps in initial and continuing teacher education in the early years, regarding the use of games in Mathematics teaching, and weaknesses related to such use in the classroom, insofar as the game is not generally used as Instrument of mediation of learning. In the observed practice there were no research or problem solving activities related to the games that would potentiate the knowledge formation by the participants and, in addition, the way games are proposed in the textbooks analyzed is, in general, inadequate, constituting an activity Little relevant to the teacher's practice, if not complemented or resized. Our study did not aim to make generalizations based on the conclusions we reached, from the selected clipping, but alert about the risk of recommending the use of mathematical teaching methodologies without the theoretical and formative input that needs to precede this use in the classroom of class.